DYNAMIC COMPUTER SIMULATION OF CONCRETE ON DIFFERENT LEVELS OF THE MICROSTRUCTURE – PART 2 - Piet Stroeven; Martijn Stroeven (Image Analysis and Stereology, 2011)
The establishment of an experimental basis for the dependence of a mechanical property on certain structural features (and the associated micro-mechanical properties) would require extensive, cumbersome and complicated testing: mechanical testing for defining the very property, quantitative (section) image analysis and stereological three-dimensional assessment of the relevant structural features. 'Realistic' simulation of material structure by computer would therefore offer an interesting alternative. This paper introduces the SPACE system (Software Package for the Assessment of Compositional Evolution) as the most recent development in this field. It has been developed to assess the composition as well as configuration characteristics of dense random packing situations in opaque materials. This paper presents an introduction to the system and will thereupon highlight by means of illustrative examples of typical applications on different levels of the microstructure the system's capabilities. Although only a single application can be presented in this framework, they all concern areas of major engineering interest.